Differential effects of Wevoflurane, Isoflurane, and Halothane on Ca2+ release from the sarcoplasmic reticulum of skeletal muscle - Kunst, Gudrun; Graf, Bernhard M.; Schreiner, Rupert; Martin, Eike; Fink, Rainer (Anesthesiology, 1999)
Although malignant hyperthermia after application of sevoflurane has been reported, little is known about its action on intracellular calcium homeostasis of skeletal muscle. The authors compared the effect of sevoflurane with that of isoflurane and halothane on Ca2+ release of mammalian sarcoplasmic reticulum and applied a novel method to quantify Ca2+ turnover in permeabilized skeletal muscle fibers.Liquid sevoflurane, isoflurane, and halothane at 0.6 mM, 3.5 mM, and 7.6 mm were diluted either in weakly calcium buffered solutions with no added Ca2+ (to monitor Ca2+ release) or in strongly Ca2+ buffered solutions with [Ca2+] values between 3 nM and 24.9 microm for [Ca+]-force relations. Measurements were taken on single saponin skinned muscle fiber preparations of BALB/c mice. Individual [Ca2+]force relations were characterized by the Ca2+ concentration at half-maximal force that indicates the sensitivity of the contractile proteins and by the steepness. Each force transient was transformed directly into a Ca2+ transient with respect to the individual [Ca2+]-force relation of the fiber.At 0.6 mM, single force transients induced by sevoflurane were lower compared with equimolar concentrations of isoflurane and halothane (P < 0.05). Similarly, calculated peak Ca2+ transients of sevoflurane were lower than those induced by equimolar halothane (P < 0.05). The Ca2+ concentrations at half maximal force were decreased after the addition of sevoflurane, isoflurane, and halothane in a concentration-dependent manner (P < 0.05).Whereas sevoflurane, isoflurane, and halothane similarly increase the Ca2+ sensitivity of the contractile apparatus in skeletal muscle fibers, 0.6 mM sevoflurane induces smaller Ca2+ releases from the sarcoplasmic reticulum than does equimolar halothane.
2+ ist im Titel hochgestellt
Gesehen am 27.04.2021